Interview with Mr. Shanker Prasad Koirala, Secretary, Ministry of Water Resources (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Mr. Shanker Prasad Koirala granted an interview toMr. Jeewan P. Thanju, Editor-in-Chief of HYDRO Nepal. He isdetermined for rapid development of hydro power sector in Nepalby mustering support from all quarters. Excerpts from aninterview:-Hydro Nepal: Journal of Water, Energy and Environment Issue No. 3, January, 2008 Page 57-59